Use of medicinal plants by people with hypertension - Marília Gabrielle Santos Nunes; Amanda de Oliveira Bernardino; René Duarte Martins (Rev Rene)
Objective: to describe the use of medicinal plants in the treatment of high blood pressure for people with hypertension enrolled in the Family Health Program in a city in Pernambuco State. Methods: a descriptive study, whose data were obtained through semi-structured interview script applied to 172 patients. Results: the use of medicinal plants for hypertension control was reported by 39.5%, of which 57.4% used only one medicinal plant. Among the species cited, there was predominant use of chayote [Sechium edule (Jacq.) Sw.-34.8%]. Conclusion:medicinal plants constitute an adjunctive therapy in the treatment of hypertension. However, there is need for monitoring of handling and listed species.